2013 13th Iranian Conference on Fuzzy Systems (IFSC) 2013
DOI: 10.1109/ifsc.2013.6675687
|View full text |Cite
|
Sign up to set email alerts
|

ANFIS-based wrapper model gene selection for cancer classification on microarray gene expression data

Abstract: This paper proposes a gene selection framework, based on wrapper model with neuro-fuzzy approach for cancer classification. ANFIS as a classifier for selected genes from Particle Swarm Optimization (PSO) or Genetic Algorithm (GA) methods applies on six datasets of microarray gene expression data for different cancers. ANFIS is compared with three other classifiers which are Support Vector Machine (SVM), K-Nearest Neighbour (KNN) and Classification And Regression Trees (CART). ANFIS gives the best results for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…They reported that the ANFIS structure they created constituted 97.08% of the accuracy of allocating individuals to 'snoring', 'sleeping' or 'silent' classes. Mahmoudi et al (31) aimed to compare the performances of the ANFIS structure in classification of individuals into cancer types using a total of six microchip gene expression data sets for breast, blood, colon, prostate, lung and lymphoma cancers and the performance of the support vector machine, k-nearest neighborhood and classification and regression trees methods. They found that the highest classification performance among the models they created separately for all cancer data sets was mostly due to the non-hierarchical fuzzy logic method.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the ANFIS structure they created constituted 97.08% of the accuracy of allocating individuals to 'snoring', 'sleeping' or 'silent' classes. Mahmoudi et al (31) aimed to compare the performances of the ANFIS structure in classification of individuals into cancer types using a total of six microchip gene expression data sets for breast, blood, colon, prostate, lung and lymphoma cancers and the performance of the support vector machine, k-nearest neighborhood and classification and regression trees methods. They found that the highest classification performance among the models they created separately for all cancer data sets was mostly due to the non-hierarchical fuzzy logic method.…”
Section: Discussionmentioning
confidence: 99%